Sensor/Antenna Interface IC for Implantable Biomedical Monitoring System - Lin, Ji-Yan; Chen, Hsiao-Chin; Yen, Ming-Yu (IEEE transactions on microwave theory and techniques, 2018)
An interface IC for medical implants is implemented by using RF techniques of carrier synthesis and wireless powering. An external RF signal at 1.608 GHz is shared by an RF-dc converter and an injection-locked divide-by-four circuit, where most of the RF energy goes to the former for RF energy harvesting and the rest of it serves as the injection signal for the latter to generate a low-phase-noise carrier at 402 MHz. Through an on-chip digital control unit and a successive approximation register analog-to-digital converter, biomedical signal in digital form can be obtained and then used to control the bias voltages of a power amplifier (PA) to perform the OOK modulation for wireless transmission. It requires an input level of 8 dBm to operate the chip. The 402-MHz carrier exhibits a phase noise of −136.7 dBc/Hz at an offset frequency of 1 MHz and the PA delivers an output power of −19.7 dBm.